(untitled) (Research, Society and Development, 2025)
Objective: To map the nursing care provided to newborns in neonatal near miss (NNM) situations during hospital stay. Method: This is a scoping review protocol developed according to the Joanna Briggs Institute (JBI) methodology and registered on the Open Science Framework platform. The research question was constructed using the PCC strategy (Population, Concept, and Context). Primary and secondary studies that address nursing care for newborns up to 28 days of life who survived NNM events in specialized hospital settings will be included. The literature search will be conducted in the Medline, LILACS, BDENF, SciELO, Web of Science, and Scopus databases using controlled descriptors and free terms, without time restrictions. Study selection and data extraction will be conducted independently by two reviewers with the support of EndNote and Rayyan software. The data will be organized and submitted to a narrative synthesis. Expected results: It is expected that the findings of this review will contribute to the systematization of nursing care for newborns in NNM situations, improve neonatal care quality, and guide future scientific research in neonatal nursing.